Sifat-sifat Khabariyah dalam Hadis-hadis Nabi Saw. (Kajian terhadap Syarah Imam al-Qasthalani dalam Kitab Irsyâd al-Sâri Syarah Shahih al-Bukhari) - Ikhwani, Ahmad (AL-DZIKRA: JURNAL STUDI ILMU AL-QUR'AN DAN AL-HADITS, 2023)
AbstractOne form of our belief in Allah is to believe in the qualities that Allah has, that all the characteristics that He has are not the same as the characteristics that exist in His creatures, such as yad, wajh, 'ain and others as if they attribute human characteristics to Allah. . This research aims to examine the hadith about the characteristics of Khabariyyah in the book Irsyâd al-Sâri li Syarh Shahîh al-Bukhari written by Imam Al-Qasthalani using the Asy'ariyyah method approach. The research method used is a type of library research (libari research) which focuses on the book Irsyâd al-Sâri li Syarh Shahîh al-Bukhari. From the results of this research, it was found that when al-Qasthalani understood the Khabariyah hadith, he used the Asy'ariyyah school-style method while still prioritizing the credibility of the hadith scholars when he found there were hadiths that were not in accordance with the Ash'ariyyah method.Keywords: Ash'ariyyah method; al-Qasthalani; Irsyâd al-Sâri li Syarh Shahîh al-Bukhari; the nature of the Khabariyyah. AbstrakSalah satu bentuk keyakinan kita kepada Allah adalah mengimani sifat-sifat yang dimiliki oleh Allah, bahwa segala sifat yang dimilikiNya tidaklah sama dengan sifat yang ada pada makhluknya, seperti yad, wajh, ‘ain dan lainnya seolah-olah menyematkan sifat-sifat manusia kepada Allah. Penelitian ini bertujuan untuk mengkaji hadis tentang sifat-sifat khabariyyah dalam kitab Irsyâd al-Sâri li Syarh Shahîh al-Bukhari yang dikarang oleh imam Al-Qasthalani dengan pendekatan metode Asy’ariyyah. Metode penelitian yang digunakan dengan jenis penelitian kepustakaan (libari research) yang terfokus pada kitab Irsyâd al-Sâri li Syarh Shahîh al-Bukhari. Dari hasil penelitian ini ditemukan bahwa bahwa al-Qasthalani ketika memahami hadis khabariyah tersebut menggunakan metode ala madzhab Asy’ariyyah dengan tetap mengutamakan kredibilitas para ulama hadis ketika ditemukan ada hadis yang secara dhahir tidak sesuai dengan metode asy’ariyyah. Kata Kunci: al-Qasthalani; Irsyâd al-Sâri li Syarh Shahîh al-Bukhari; metode asy’ariyyah; sifat Khabariyyah.